Răspuns :
[tex](\frac{1}4} )^{5-x} = 2^{x+3}[/tex]
-logaritmezi in baza e;
-exponentul iese in fata;
[tex](5-x)*ln(1/4)=(x+3)*ln(2)[/tex]
*ln(a/b)=ln a - ln b;
[tex](5-x)ln(1)-(5-x)ln2^{2} =(x+3)*ln(2)[/tex]
ln(1)=0;
[tex]-2(5-x)ln(2)=(x+3)ln(2)[/tex]
-impartim cu ln 2
[tex]-10+2x=x+3[/tex]
[tex]x=13[/tex]
verificare:
[tex](\frac{1}{4} )^{-8} =2^{16} [/tex]
[tex]({2^{-2}})^{-8}=2^{16} [/tex]
[tex]2^{16}=2^{16} [/tex]
-logaritmezi in baza e;
-exponentul iese in fata;
[tex](5-x)*ln(1/4)=(x+3)*ln(2)[/tex]
*ln(a/b)=ln a - ln b;
[tex](5-x)ln(1)-(5-x)ln2^{2} =(x+3)*ln(2)[/tex]
ln(1)=0;
[tex]-2(5-x)ln(2)=(x+3)ln(2)[/tex]
-impartim cu ln 2
[tex]-10+2x=x+3[/tex]
[tex]x=13[/tex]
verificare:
[tex](\frac{1}{4} )^{-8} =2^{16} [/tex]
[tex]({2^{-2}})^{-8}=2^{16} [/tex]
[tex]2^{16}=2^{16} [/tex]
(\frac{1}4} )^{5-x} = 2^{x+3}
-logaritmezi in baza e;
-exponentul iese in fata;
(5-x)*ln(1/4)=(x+3)*ln(2)
*ln(a/b)=ln a - ln b;
(5-x)ln(1)-(5-x)ln2^{2} =(x+3)*ln(2)
ln(1)=0;
-2(5-x)ln(2)=(x+3)ln(2)
-impartim cu ln 2
-10+2x=x+3
x=13
verificare:
(\frac{1}{4} )^{-8} =2^{16}
({2^{-2}})^{-8}=2^{16}
2^{16}=2^{16}